Program Kemitraan Masyarakat: Pembuatan Identitas Merek dan Pembinaan Penerapan Branding untuk Meningkatkan Penjualan Usaha Mikro Kuliner Kupat Tahu Padalarang di Kecamatan Batujajar - Tintin Suhaeni; Sri Raharso; Ivon Sandya Sari Putri; Abdul Malik Sayuti; Tangguh Dwi Pramono; Marceilla Suryana; Chandra Budhi Septiyandi (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2020)
This community partnership program aims to develop the Kupat Tahu Padalarang business in Kecamatan Batujajar, Jawa Barat by building a business brand identity, personal branding, excellent service, and good customer communication. The survey was conducted to obtain information on brand awareness, business conditions, and customer satisfaction before and after the program was implemented. The creation of a business brand identity starts with creating logo, banner, product packaging, employee uniforms, and structuring the business environment. Personal branding itself is created through the development of excellent service and good and friendly customer communication. Business brands that have been created have also been registered to protect business actors from imitating them. The brand is a capital that can be developed by business actors to be used in promotion on social media in order to increase business brand equity